HIV in MOTION: a community of practice on physical rehabilitation for and by people living with HIV and their allies - Ibáñez-Carrasco, Francisco; Jiancaro, Tizneem; Torres, Brittany; McDuff, Kiera; Da Silva, George; Lindsay, Joanne; Price, Colleen; Islam, Shaz; Bradford, Glen; O'Brien, Kelly K. (Frontiers in Rehabilitation Sciences, 2023)
Ibáñez-Carrasco F*1, Lead author, literature search, outlines, drafts, and final writing; Jiancaro T, provided extensive review, McDuff K2 and Torres B2, both research coordinators contributed with literature search and feedback and coordinating draft discussion meetings, Da Silva G2, Price C, Islam S, Lindsay J, Bradford, Glen are non-academic authors who provided extensive support and written feedback from the "patient" and lived experience perspectives, George also collected all data from electronic evaluation surveys; and O'Brien KK2,3,4, co-lead author, provided extensive writing and evaluation.